Signifikansi Perang Siber Dalam Konflik Modern Rusia-Ukraina Studi Kasus: Wizard Spider VS It Army - Imma, Karisma; Burhanuddin, Agussalim (Jurnal Ilmu Sosial dan Humaniora, 2023)
The escalation of the conflict between Russia - Ukraine began to experience significant changes to a broad scope and no longer only emphasized the security system on the use of military aspects. Both Russia and Ukraine have made cyberspace important as another part of modern conflicts in the form of cyber wars by focusing on cyber security defense strategies. The significance of this conflict then prompted the creation of the Wizard Spider and the IT Army as cyber-specific organizations as well as supporting actors who play a direct role in the conflict realm. This study uses a qualitative descriptive research method by collecting data from literature studies. The results of the study found that the cyber security system as an attack strategy in the Russia – Ukraine conflict has encouraged the creation of a more modern conflict through confrontational actions in cyberspace carried out by Wizard Spider and the IT Army. This organization has indirectly become a dominant actor through its role in carrying out cyber threats and attacks as well as being a determining actor in the direction of the Russia-Ukraine cyber war conflict.